2015
DOI: 10.1039/c4tc02751e
|View full text |Cite
|
Sign up to set email alerts
|

Broadband enhanced fluorescence using zinc-oxide nanoflower arrays

Abstract: ZnO nanoflower arrays have significantly higher fluorescence enhancement than ZnO nanorod arrays, with broadband enhancement capability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 29 publications
1
32
0
Order By: Relevance
“…33,40 Using finite difference time domain (FDTD) analysis, our group previously investigated electric field enhancement due to aligned ZnO NR arrays of 70 nm diameter, excited by a normally incident electric field at wavelengths of 530 nm and 650 nm, respectively. 12 The work showed that the electric field enhancement could account for the increase in fluorescence for aligned NR arrays, which was less than 1 order of magnitude. In the same study the fluorescent enhancement due to NFs was also studied under the same conditions and was found to be about 4 times higher than for aligned NRs, once corrected for increased surface area available for fluorophore attachment.…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…33,40 Using finite difference time domain (FDTD) analysis, our group previously investigated electric field enhancement due to aligned ZnO NR arrays of 70 nm diameter, excited by a normally incident electric field at wavelengths of 530 nm and 650 nm, respectively. 12 The work showed that the electric field enhancement could account for the increase in fluorescence for aligned NR arrays, which was less than 1 order of magnitude. In the same study the fluorescent enhancement due to NFs was also studied under the same conditions and was found to be about 4 times higher than for aligned NRs, once corrected for increased surface area available for fluorophore attachment.…”
Section: Introductionmentioning
confidence: 97%
“…Fluorescence-based biosensing [1][2][3][4] is a widely adopted approach for early-stage diagnosis but still faces challenges, 5,6 such as sensitivity, high throughput capability and adjustable sensing signal output. ZnO 7-9 is a semiconducting piezoelectric material with a direct band gap (3.37 eV) and large excitonbinding energy (60 mV) 7 which can form various nanostructures [6][7][8][10][11][12][13][14][15][16][17][18][19][20][21][22][23] via numerous established processes. Its usefulness has been demonstrated in a broad range of applications, such as solar cells 11,24 , piezoelectric nanogenerators 25,26 , light emitters 27 and optical waveguides 28 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations